PENGARUH LIGHT SHELF STATIS TERHADAP KINERJA PENCAHAYAAN ALAMI KANTOR OPEN-PLAN - Hasya, Astrini Hadina; Nastiti, Ratna Andriani; Rachman, R. Ayu Firdausi Novira; Dewi, Riza Septriana; Artito, Ihza Rangga (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
An office with an open-plan system is a popular building today with the complexity of activities and user needs. The advantages of saving space and making a spacious impression make open-plan offices popular. The main activity of the office as a place to work requires optimal daylighting to accommodate all its main activities during office hours. This study is a quasi-experimental research evaluating natural lighting performance in office buildings. The consideration of office building was chosen based on the general open-plan office criteria. The problem of uneven daylighting in the office space demands a system to increase daylighting performance. The use of lightshelf as a natural shading system is proposed as an alternative to increase daylighting performance, which is computationally simulated using Ecotect with the Radiance plug-in. Data collection techniques are carried out through computer simulation modeling and literature studies. It is hoped that the results of this study can add insight and be used as an alternative to daylight shading systems.